Peningkatan Pemahaman Dan Praktik Siswa Kelas IV SD Dalam Menyampaikan Salam Melalui Pendekatan Pembelajaran Aktif - Misrijal Rianti, Elsi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the use of audio-visual media in improving the learning outcomes of 4th-grade students at SD Negeri 10 Lubuk Layang. The research was conducted in three cycles, each involving preparation, implementation, observation, evaluation, and reflection stages. The results show that there was an improvement in students' understanding of the learning material after using audio-visual media, although the increase observed in Cycles I and II was not significant. In Cycle III, more students reached the "Expert" category, although there is still room for improvement. The study concludes that the use of audio-visual media can enhance learning outcomes, but further development is needed for more optimal results.